Peran Kepemimpinan dalam Pengelolaan Konflik di Organisasi Lembaga Pendidikan (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
Leadership plays a crucial role in conflict management within educational organizations. Conflicts, whether interpersonal or structural, are inevitable due to differences in backgrounds, interests, and objectives among individuals within the organization. This study aims to analyze the role of leadership in identifying, managing, and effectively resolving conflicts. Using a qualitative descriptive approach, the research explores leadership styles such as transformational and collaborative leadership, which contribute to constructive conflict management. The results of the study indicate that leaders in educational organizations act as mediators, facilitators, and decision-makers capable of addressing conflicts through open and dialogical communication approaches. Furthermore, an inclusive, transparent, and justice-based organizational culture is identified as a key element in preventing future conflicts. Effective conflict management not only resolves issues but also strengthens interpersonal relationships and enhances overall organizational performance.